1974
DOI: 10.1093/clinchem/20.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Relative Affinity of Hemoglobin S and Hemoglobin A for Carbon Monoxide and Oxygen

Abstract: The relative affinity constants of hemolysates from individuals with hemoglobins A, S, or AS have been measured at 37 and 26 ° C. Observed values of all hemoglobin types were the same at both temperatures, K37 = 230, K26 = 296. Control measurements on whole blood containing Hb A gave values of K37 = 222. The small but significant difference between K37 values measured in whole blood and in hemolysates may be a result of the greater increase of MetHb in the hemolysates during the in vitro equilibration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…However, we found that COHb concentration was not a predictive factor for DNS, similar to several other reports . The affinity of hemoglobin for CO is approximately 220 times greater than that for oxygen . Therefore, CO rapidly binds to hemoglobin after exposure and is transferred to the intracellular space where it binds myoglobin and mitochondrial cytochrome oxidase .…”
Section: Discussionsupporting
confidence: 87%
“…However, we found that COHb concentration was not a predictive factor for DNS, similar to several other reports . The affinity of hemoglobin for CO is approximately 220 times greater than that for oxygen . Therefore, CO rapidly binds to hemoglobin after exposure and is transferred to the intracellular space where it binds myoglobin and mitochondrial cytochrome oxidase .…”
Section: Discussionsupporting
confidence: 87%
“…Such a disturbance of mitochondrial respiratory chain function could lead to a decay in mitochondria energy production and, eventually, to cellular injury or dysfunction, especially in “high metabolic rate” tissues exposed to CO such as the central nervous system, heart muscle or skeletal muscle. Indeed, muscular weakness and impaired heart function have been reported and demonstrated in CO poisoning (Tritapepe et al 1998; Raub et al 2000; Yanir et al 2002) and in heavy smokers (Örlander et al 1979; Gvozdjakova et al 1984). On the other hand, the disturbance in mitochondrial respiratory chain function may also lead to a major production of reactive oxygen species (Cadenas & Davis 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Carbon monoxide (CO) is a potent vertebrate toxin that binds 200-300 times more tightly to haemoglobin than O 2 (Rodkey et al, 1974), blocking oxygenation of the tissues and inhibiting the mitochondrial electron transport chain by binding cytochromes, with potentially lethal effects. This toxicity extends even to the microbial world, with the ability of CO to bind to and inhibit metalloenzymes as well as interrupt electron transport chains.…”
Section: Introductionmentioning
confidence: 99%